An Overview of The Level of Occupational Stress of Anesthesiologists In The Surgical Room of The Hospital In The Banyumas District Area: English - Assyifa, Ibnu; Sukmaningtyas, Wilis; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2023)
Background: Every profession and employee in both developed and developing countries is affected by occupational stress, which is a global problem. Due to the great burden and responsibility of safeguarding human lives, the anesthesia care profession is particularly vulnerable to stress. And high levels of occupational stress can cause health problems, such as mental and behavioral disorders such as fatigue, anxiety, and depression, as well as other physical disorders such as cardiovascular disease and musculoskeletal disorders that affect service functions. The role of expert anesthesiologist has a function in pre, intra, post anesthesia care services and emergency management. Objective: To identify the characteristics of anesthesiologist's work stress level based on age, gender, working period, working hours and latest education in the surgical room. Methods: This research is descriptive quantitative with a cross sectional approach. The study population was 39 respondents, the focus of observation in this study was a description of the stress level of anesthesia administrators in the surgical room of the Banyumas Regency Hospital. Results: This study shows the level of stress with mild stress category with a total of 19 respondents with a percentage (48.7%) and moderate work stress as many as 4 respondents with a percentage (10.3%). Conclusion: The results of this study indicate the presence of mild and moderate work stress in surgical room anesthesiologists at the Banyumas Regency Regional Hospital.